Travail Enseignant, Résilience Et Formation - Oumelili, Hamid (جامعة الوادي - University of Eloued, 2023)
Résumé : Avec la dégradation de la qualité éducative en Algérie et les conditions d'enseignement dues à la crise sanitaire COVID 19, les enseignants se retrouvent face à de nombreux défis et un épuisement professionnel. Devant ces perturbations, il est devenu nécessaire d'intégrer le processus de résiliation dans la formation continue des enseignants. L’objectif de cet article se résume à la clarification des constructions identitaire tant sur le plan personnel ou professionnel, en liant le vécu intime de l'enseignant (qui suis-je) et le développement de ses compétences professionnelles (qui voudrais-je être).With the deterioration of educational quality in Algeria and the teaching conditions due to the COVID 19 health crisis, the teachers have found themselves facing many challenges and burnout. In the face of these tensions, it has become necessary to integrate the process of termination into the continuing education of teachers. The objective of this article comes down to clarifying identity constructions both on a personal and professional level, by linking the intimate experience of the teacher (who am I) and the development of his professional skills (who would I like to be).
مقال
Keywords: la formation ; processus de résilience ; enseignant ; bien-être; Training; resilience process; teacher; well-being